Art as a laboratory – Guy Ben-Ary’s work - Szykowna, Sylwia (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Szykowna Sylwia, Art as a laboratory – Guy Ben-Ary’s work. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 115–124. ISSN 1731-450X. DOI 10.14746/i.2019.34.07. The present paper deals with the work of an Israeli artist, Guy Ben-Ary. His work is a prime example of artistic practice in the field of bio art. Bio art provokes critical thinking about the place and role of people in today’s world. The main purpose of the article is to describe changes in contemporary artistic practices within the framework of art as a laboratory, the aim of which is to study reality.